An opportunistic Search for Extraterrestrial Intelligence (SETI) with the Murchison Widefield Array - Tingay, Steven; Tremblay, C.; Walsh, Andrew; Urquhart, Ryan (Institute of Physics Publishing, 2016)
© 2016. The American Astronomical Society. All rights reserved. A spectral line image cube generated from 115 minutes of MWA data that covers a field of view of 400 sq, deg. around the Galactic Center is used to perform the first Search for ExtraTerrestrial Intelligence (SETI) with the Murchison Widefield Array (MWA). Our work constitutes the first modern SETI experiment at low radio frequencies, here between 103 and 133 MHz, paving the way for large-scale searches with the MWA and, in the future, the low-frequency Square Kilometre Array. Limits of a few hundred mJy beam-1 for narrowband emission (10 kHz) are derived from our data, across our 400 sq. deg. field of view. Within this field, 45 exoplanets in 38 planetary systems are known. We extract spectra at the locations of these systems from our image cube to place limits on the presence of narrow line emission from these systems. We then derive minimum isotropic transmitter powers for these exoplanets; a small handful of the closest objects (10 s of pc) yield our best limits of order 1014 W (Equivalent Isotropic Radiated Power). These limits lie above the highest power directional transmitters near these frequencies currently operational on Earth. A SETI experiment with the MWA covering the full accessible sky and its full frequency range would require approximately one month of observing time. The MWA frequency range, its southern hemisphere location on an extraordinarily radio quiet site, its very large field of view, and its high sensitivity make it a unique facility for SETI.